Mental health problems, interpersonal trust, and socio-cultural correlates of corruption perception in Ghana - Anyan, Frederick; Andoh-Arthur, Johnny; Adjei, Stephen Baffour; Akotia, Charity Sylvia (Frontiers in Public Health, 2024)
This study examines the overall levels and effects of corruption perception on mental health while controlling for the effect of interpersonal trust as a routine covariate in studies of corruption. Participants (N = 730; 60.8% Men; Mean age = 22.13, SD = 3.66) were invited to answer a cross-sectional survey. Group mean difference tests and network analysis were performed. Women, urban dwellers, and those who showed moderate religiosity, and lower nationality reported the highest levels of corruption perception, but the effect on mental health problems was stronger for higher religiosity. The perception that politicians and government officials are corrupt emerged as the most influential to link other corruption perceptions (e.g., state institutions are corrupt). Witnessing corruption among state institutions and government officials and the perception that the rich in society can influence any state institutions and actors showed the strongest and broadest links to depression and anxiety symptoms. The findings suggest that there may be substantial effect of corruption on mental health problems than trust in interpersonal relationships. The relatively high poverty rate in Ghana may explain why those who do not have the financial means or personal connections to meet the demands of bribery and corruption experience a sense of helplessness associated with mental health problems when they perceive that the rich in society can influence state institutions and actors for personal gains. Furthermore, the tendency to remain silent to protect others from being exposed in corruption in order to maintain relationships, or to expose them to ruin relationships, or conform to a culture of corruption either in solidarity or fear of victimisation may create a psychological burden that may be associated with mental health problems. The implications for reconceptualising corruption as a key social determinant of public mental health are discussed.